As práticas informacionais na produção científica dos pesquisadores na pós-graduação - Maíra Prado da Silva (2020)
The research problematized the subject's relationship with the production of knowledge, seeking to understand the informational practices of researchers in scientific production and their communication, based on the approach of researchers in the Postgraduate Program in Social Communication at the Federal University of Minas Gerais (UFMG). The objectives is identifying the information resources used by researchers in the scientific production process; understand the meanings attributed by the researchers in the strategies used; and to analyze how researchers perceive the effects of postgraduate organization on scientific production and communication. Pierre Bourdieu's praxiological theory was used as a reference, mainly the notion of scientific field, agents and institutions. The research had a qualitative approach, through a case study, in which content analysis was used. To collect the data, 12 semi-structured interviews were carried out. The analysis of the data showed that the researchers use tools and strategies that help them in the search and retrieval of information, with reliability being the requirement that supports the sources of information. The researchers' daily activities and actions are outlined by conventional scientific practices and permeate affective, social and political perceptions when producing knowledge. The situations experienced by researchers when producing and communicating awaken the movement in favor of what has little space in the field, such as the search for non-hegemonic knowledge, other means of publication and communication. At the same time, the researchers assimilate the functioning of the scientific field, represented by the institutions with their rules and norms that they must follow in order to remain active in the research. This reflects in the search, use and sharing of information by researchers, outlining the research process, through information resources, the selection of authors in the literature, type of publication and language, communication channels, and the sharing and storage of information. In this process, it opens up the possibility for new initiatives to be inserted, such as the use of other fields of dialogue, publications and means to locate information, mainly for those researchers who are critical of the structure of the scientific field.